Genome-wide analysis of phytochrome-interacting factor (PIF) families and their potential roles in light and gibberellin signaling in Chinese pine - Yingtian Guo; Chengyan Deng; Guizhi Feng; Dan Liu (BMC Genomics)
Abstract Phytochrome-interacting factors (PIFs) are a subgroup of transcription factors within the basic helix-loop-helix (bHLH) family, playing a crucial role in integrating various environmental signals to regulate plant growth and development. Despite the significance of PIFs in these processes, a comprehensive genome-wide analysis of PIFs in conifers has yet to be conducted. In this investigation, three PtPIF genes were identified in Chinese pine, categorized into three subgroups, with conserved motifs indicating the presence of the APA/APB motif and bHLH domain in the PtPIF1 and PtPIF3 proteins. Phylogenetic analysis revealed that the PtPIF1 and PtPIF3 proteins belong to the PIF7/8 and PIF3 groups, respectively, and were relatively conserved among gymnosperms. Additionally, a class of PIF lacking APA/APB motif was identified in conifers, suggesting its function may differ from that of traditional PIFs. The cis-elements of the PtPIF genes were systematically examined, and analysis of PtPIF gene expression across various tissues and under different light, temperature, and plant hormone conditions demonstrated similar expression profiles for PtPIF1 and PtPIF3. Investigations into protein-protein interactions and co-expression networks speculated the involvement of PtPIFs and PtPHYA/Bs in circadian rhythms and hormone signal transduction. Further analysis of transcriptome data and experimental validation indicated an interaction between PtPIF3 and PtPHYB1, potentially linked to diurnal rhythms. Notably, the study revealed that PtPIF3 may be involved in gibberellic acid (GA) signaling through its interaction with PtDELLAs, suggesting a potential role for PtPIF3 in mediating both light and GA responses. Overall, this research provides a foundation for future studies investigating the functions of PIFs in conifer growth and development.